OTUB1-mediated inhibition of ubiquitination: a growing list of effectors, multiplex mechanisms, and versatile functions - Wu, Miaomiao; Sun, Lidong; Song, Tanjing (Frontiers in Molecular Biosciences, 2024)
Protein ubiquitination plays a pivotal role in protein homeostasis. Ubiquitination may regulate stability, activity, protein-protein interaction and localization of a protein.Ubiquitination is subject to regulation by two groups of counteracting enzymes, the E3 ubiquitin ligases and deubiquitinases. Consistently, deubiquitinases are involved in essentially all biological processes. OTUB1, an OTU-family deubiquitinase, is a critical regulator of development, cancer, DNA damage response and immune response. OTUB1 antagonizes ubiquitination of a wide-spectrum of proteins through at least two different mechanisms. Besides direct deubiquitination, OTUB1 can also inhibit ubiquitination by non-canonically blocking ubiquitin transfer from certain ubiquitinconjugases (E2). In this review, we start with general background of protein ubiquitination and deubiquitination. Next we introduce basic characteristics of OTUB1 and then elaborate on updated biological functions of OTUB1. Afterwards, we discuss potential mechanisms underlying the versatility and specificity of OTUB1 function. In the end, we will discuss the perspective that OTUB1 can be a potential therapeutic target for cancer.